On inexact Tikhonov and proximal point regularization methods for pseudomonotone equilibrium problems - Phạm, Gia Hưng (Trường Đại học Đà Lạt, 2012)
We investigate the inexact Tikhonov and proximal point regularization methods for pseudomonotone equilibrium problems. In this ease, the regularized subproblems may be not strongly monotone, even not pseudomonotone. However, any iterative sequence of the regularized subproblems tends to the same solution of the original problem whichis nearest to the starting point for the Tikhonov method.